SEKTOR UNGGULAN DAN PERTUMBUHAN EKONOMI DALAM PENGEMBANGAN POTENSI EKONOMI DI KABUPATEN SRAGEN PROVINSI JAWA TENGAH - Yofhi Septian P; Tri Nurdyastuti (STIE AUB Surakarta, 2019)
Research Objectives To determine the Stregth, Weekness, Opportunuty, Threat Boyolali Regency in2010-2016. This study uses quantitative and qualitative descriptive data using secondary data from BPS Sragen Regency in 2010-2016. The research uses quantitative analysis calculations on regional potential, economic growth, and economic structure will then be analyzed qualitatively using SWOT, LQ, shift share analysis. From the results of the study above shows the largest results of the leading sectors of service companies amounted to 1.7 and 1.9 and the lowest water management amounted to 0.11 and 0.21. The LQ table results show that the location magnitude is dominated by large traders <the supply of drinks and communication information. 3. And the lowest in the financial sector is <transportation and mining of 0. Sragen regency is one of the districts in Central Java which has a very strategic location. Geographically, this regency is a crossing point for regional transportation routes between the cities of Semarang, Solo and Surabaya. The economic growth rate of Sragen Regency in 2016 was recorded at 5.72 percent. This growth rate was recorded as the fourth largest in Central Java Province and the highest among all regencies / cities in the ex-residency area of Surakarta. In addition, the rate of economic growth in Sragen Regency in the last few years has always been above the average growth rate of the Central and National Provinces of the Province.